Viable Cooperation or Unscrupulous Service? Motivations for Albert Bereczky’s Activity in Church Governance - LÁNYI, Gábor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
Albert Bereczky is one of the controversial figures in the 20th-century history of the Hungarian Reformed Church. Bereczky was a genuine and authentic leader of those who fought for the inner spiritual renewal of the church between the two world wars, a church organizer, a well-known and respected preacher, who saved many by risking his life during the deportation of Hungarian Jews to extermination camps, for which he was posthumously awarded the honorary title “Righteous Among the Nations” from the Yad Vashem. However, the communist state apparatus established after World War II found in him the person who, by placing him at the head of the Reformed Church, could bring about a radical reduction of the public and social role of the Church almost without any resistance. So, the question arises: how and why could Bereczky, whose Christian commitment was hard to question, become the servant of the dictatorial state apparatus with its atheistic ideology? Our study attempts to record the possible intrinsic and extrinsic motivations that might explain this dilemma, while also providing a general insight into Albert Bereczky’s life.